Plasma oxytocin explains individual differences in neural substrates of social perception - Lancaster, Katie; Carter, C. Sue; Pournajafi-Nazarloo, Hossein; Karaoli, Themistoclis; Lillard, Travis S.; Jack, Allison; Davis, John M.; Morris, James P.; Connelly, Jessica J. (Frontiers in Human Neuroscience, 2015)
The neuropeptide oxytocin plays a critical role in social cognition and behavior. A number of studies using intranasal administration have demonstrated that oxytocin improves social perception. However, little is known about the relationship between individual differences in endogenous levels of oxytocin and social cognition. In the current study, we assessed the relationship between endogenous oxytocin and brain activity during an animacy perception paradigm. Thirty-seven male participants underwent scanning and provided a blood sample for oxytocin analysis. In line with previous research, perception of animacy was associated with activations in superior temporal sulcus, inferior frontal gyrus, and medial prefrontal cortex (mPFC). Notably, participants’ levels of plasma oxytocin robustly predicted activation in areas critical for social cognitive processes, such that higher oxytocin levels were related to increased activity in dorsal mPFC, ventral mPFC, dorsolateral PFC, superior temporal gyrus, and temporoparietal junction, suggesting differential processing of social stimuli. Together these results show that stable variations in endogenous oxytocin levels explain individual differences in social perception.